ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN DANA DESA DI NAGARI TANJUNG ALAM KECAMATAN TANJUNG BARU TAHUN 2022 - Rahim, Febria; Melia, Yeni; Amran, Elsa Fitri; Putri, Silvani Asrina (Jurnal Akuntansi Syariah (JAkSya), 2024)
The aim of this research is to determine the accountability and transparency of village fund management in Nagari Tanjung Alam, Tanjung Baru District. The type of research used is field research. The method used is descriptive with a qualitative approach. The data collection technique in this research is through interviews by collecting documents. The results of the research show that the principles of accountability and transparency in the management of village funds in Nagari Tanjung Alam have been implemented in accordance with Permendagri Number 20 of 2018. In the principle of accountability, the government of Nagari Tanjung Alam at the planning, implementation, administration and accountability stages can be said to be accountable, according to the principle of transparency The Nagari Tanjung Alam government has provided information to the public through available information boards, although not all the information is fully included. In the reporting stage it cannot be said to be accountable because the Nagari Tanjung Alam Government is still late in reporting and in terms of transparency it cannot be said to be fully transparent because the Nagari Tanjung Alam Government does not provide information regarding activities that have not been completed/implemented and the remaining budget is not included on the available information boards.